Cocaine-Induced Agitated Delirium: A Case Report and Review. (January 2015) - Plush, Theodore; Shakespeare, Walter; Jacobs, Dorian; Ladi, Larry; Sethi, Sheeba; Gasperino, James
Cocaine use continues to be a major public health problem in the United States. Although many of the initial signs and symptoms of cocaine intoxication result from increased stimulation of the sympathetic nervous system, this condition can present as a spectrum of acuity from hypertension and tachycardia to multiorgan system failure. Classic features of acute intoxication include tachycardia, arterial vasoconstriction, enhanced thrombus formation, mydriasis, psychomotor agitation, and altered level of consciousness. At the extreme end of this toxidrome is a rare condition known as cocaine-induced agitated delirium. This syndrome is characterized by severe cardiopulmonary dysfunction, hyperthermia, and acute neurologic changes frequently leading to death. We report a case of cocaine-induced agitated delirium in a man who presented to our institution in a paradoxical form of circulatory shock. Rapid evaluation, recognition, and proper management enabled our patient not only to survive but also to leave the hospital without neurologic sequelae.